(3GdJYdjbGJ hGdfhGOQs - (3GdgLQj , gGQhf Hf RcQjG GdgLQj, CHh Ydj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd CHh Ydi gGQhf Hf RcQjG GdgLQi (B: (3CfTOfi CHh SdjeGf GdgPdi hCHh YeQh GdRgjQi (B- (3RgjQ agO (B- (3GdLejd (B: (3hdeG CLO GdMi HjfG hde jcf OQi CMO ef Hjf HKfI aGLY s
(3BNQgG (B:s
(3eWehS de jJVM efgG BNQ GdcJGH s
(3GdfSNI GdChdis
(3HgG fXGe GdJYbjHIs
(3bWYI KGfjI ef GdfSNI GdChdis
(3ai WQJgG HNWg GWdGY GdYdGeI CMeO Hf YHO GdbGOQ Hf CMeO Hf ecJhe Hf CMeO GdbjSi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B60s
Keywords: (3GddZIs